Influence of high-dose ion implantation of NiTi equiatomic on shape memory and pseudoelastic - Pogrebnjak, A.; Bratushka, S.; Levintant-Zayonts, N.; Malikov, L. (Физическая инженерия поверхности, 2012)
This work explains the method alloying process of the TiNi thin films in addition to the shape memory properties of the TiNi thin films made by alloying the TiNi multilayer thin films. The surface layer of an equiatomic TiNi alloy, which exhibits the shape memory effect in the martensitic slate, is modified with high-dose implantation ions N⁺, Ni⁺ -N⁺, and Mo⁺ -W⁺ ions at a dose of 10¹⁷ − 10¹⁸ cm⁻² and studied by Rutherford back scattering, scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction, and by measuring the nanohardness and the elastic modulus. After double implantation ions, the hardness of the TiNi samples is 2.78 ± 0.95 GPa at a depth of 150 nm and 4.95 2.25 GPa at a depth of 50 nm; the elastic modulus is 59 GPa. The coating demonstratedthe increased corrosion resistance in acidic and alkaline media in comparison with that of the non-implanted surface. A correlation between the elemental composition, microstructure, shape memory effect, and mechanical properties of the near-surface layer in TiNi is found.